endeteksian Fraud: Analisis Komprehensif Melalui Bukti Dengan Analisis Rasio, F-Score, dan M-Score pada PT Waskita Karya (Persero) Tbk - Amelia, Lusi; Ardini, Lilis (Accounting Study Program, Universitas Ciputra Surabaya, 2024)
This research conducts a comprehensive analysis of the financial statements of PT Waskita Karya (Persero) Tbk (WSKT) with the primary objective of detecting potential fraud. Financial reporting plays a vital role in providing information about the financial position and performance of a company. However, the risk of fraud in financial statements poses a serious threat that requires special attention from various stakeholders, including shareholders, regulators, and auditors. This study utilizes a triangulation method, investigating the company's financial statements by juxtaposing findings from quantitative analysis and qualitative interpretation. By combining evidence from both approaches, the research aims to provide a more comprehensive view and sufficient evidence regarding the potential for fraud in the financial statements of WSKT. A case study is conducted on WSKT, which previously faced controversy related to alleged manipulation of financial statements. The analysis includes various financial ratios such as profitability, liquidity, activity, and solvency. Additionally, the F-Score and M-Score models are used as tools to detect potential manipulation signs based on financial data over the last ten years. The research findings encompass significant fluctuations in the company's profitability, activity, liquidity, and solvency. The results of the F-Score and M-Score analyses provide indications potentially related to the quality of financial reporting and signs of manipulation. The implications of these findings support the need for in-depth auditing and strategic improvements in financial and operational management to facilitate decision-making and further preventive measures. Limitations of the study involve time constraints and a focus solely on financial statement data. Therefore, the research proposes recommendations for further in-depth studies considering external factors, regulatory changes, and other variables that may influence the potential for fraud in the corporate context.